Peningkatan Hasil Belajar Pendidikan Pancasila pada Materi Keberagaman Sosial dan Budaya melalui Media Pembelajaran Ular Tangga - Almaidah Rifma Cahyani; Iksam; Tasya Noviandra Putri; Muhlis (Mataram University, 2026)
Low student participation during the learning process and the limited use of interactive learning media have resulted in learning outcomes in Pancasila Education, particularly on the topic of social and cultural diversity, not meeting the Minimum Learning Achievement Criteria (KKTP). This study aimed to improve students' learning outcomes in Pancasila Education on the topic of social and cultural diversity through the use of a Snakes and Ladders learning media for fourth-grade students of SD Negeri 002 Samarinda Kota. The study employed a Classroom Action Research (CAR) design conducted in two cycles, each consisting of planning, action, observation, and reflection stages. The research subjects were 32 fourth-grade students. Data were collected through observation, tests, and documentation, while quantitative data analysis was carried out by calculating the percentage of students achieving mastery learning. The findings revealed a consistent improvement in students' learning outcomes across the cycles. In the pre-cycle, the average learning outcome score was 65, with a mastery learning percentage of 31.25%. After implementing the Snakes and Ladders learning media in Cycle I, the average score increased to 73.75, with a mastery percentage of 65.62%. Further improvement was observed in Cycle II, where the average score reached 82.28 and the mastery percentage increased to 81.25%. These findings indicate that the success criterion of the study was achieved, as at least 75% of the students obtained a score of 75 or higher, in accordance with the school's KKTP. Therefore, the Snakes and Ladders learning media is effective in improving students' learning outcomes in Pancasila Education on the topic of social and cultural diversity at the elementary school level.